Reflections environment on identity in Peru - Sarango Zárate, Enrique (2022)
One of the fundamental discussions in Peru is about identity, it is sometimes wrong due to false recognition, people who often have an identity because they give it to them or people who often have a (false) identity product of someone making them believe that they are something determined. The paper’s mission is to bring out the aforementioned and point out the reasons that have led to it.